HERC1 Ubiquitin Ligase Is Required for Hippocampal Learning and Memory - Pérez-Villegas, Eva M.; Pérez-Rodríguez, Mikel; Negrete-Díaz, José V.; Ruiz, Rocío; Rosa, Jose Luis; de Toledo, Guillermo Alvarez; Rodríguez-Moreno, Antonio; Armengol, José A. (Frontiers in Neuroanatomy, 2020)
Mutations in the human HERC1 E3 ubiquitin ligase protein develop intellectual disability. The tambaleante (tbl) mouse carries a HERC1 mutation characterized by cerebellar ataxia due of adult cerebellar Purkinje cells death by extensive autophagy. Our previous studies demonstrated that both the neuromuscular junction and the peripheral nerve myelin sheaths are also affected in this mutant. Moreover, there are signs of dysregulated autophagy in the central nervous system in the tbl mouse, affecting spinal cord motor neurons, and pyramidal neurons of the hippocampal CA3 field and the neocortex. The tbl mutation affects associative learning, with absence of short- and long-term potentiation in the lateral amygdala, altered spinogenesis in their neurons, and a dramatic decrease in their glutamatergic input. To assess whether other brain areas engaged in learning processes might be affected by the tbl mutation, we have studied the tbl hippocampus using behavioral tests, ex vivo electrophysiological recordings, immunohistochemistry, the Golgi-Cox method and transmission electron microscopy. The tbl mice performed poorly in the novel-object recognition, T-maze and Morris water maze tests. In addition, there was a decrease in glutamatergic input while the GABAergic one remains unaltered in the hippocampal CA1 region of tbl mice, accompanied by changes in the dendritic spines, and signs of cellular damage. Moreover, the proportions of immature and mature neurons in the dentate gyrus of the tbl hippocampus differ relative to the control mice. Together, these observations demonstrate the important role of HERC1 in regulating synaptic activity during learning.